Procedimentos e processos: uma delicada relação na aprendizagem de discriminações por bebês - Sousa, Naiara Minto de (2013)
This dissertation was based on four empirical research reports submitted for publication in specialized journals. The empirical researches laid the foundations for a theoretical analysis on Stimulus Control and discrimination learning by children about two-yearsold. Each of the four empirical reports have adjusted procedures for teaching discrimination, which have produced: 1) simple discrimination learning by children from 10- to 20-months-old; 2) simple discrimination and discrimination reversal learning by toddlers aged 15- to 23-months; 3) rapid listener behavior learning by a toddler aged 17- to 22-months; 4) identity conditional discrimination learning by seven toddlers aged 14- to 27-months and generalization from object-object relation with an abstract stimulus pair to the photo-object and video-object relations by a toddler aged 27- to 29-months. Based on the experimental data, the processes probably involved in the rapid discrimination learning by toddlers in their everyday interactions were brought out. Concerning vocabulary acquisition, responding by exclusion and ostensive learning were emphasized. Regarding concept formation, the processes of generalization between similar stimuli and equivalence class formation between dissimilar stimuli were addressed. The challenges in defining appropriated experimental procedures for investigating discrimination acquisition by toddlers in translational research were discussed. Additionally, we were concerned on the homology between the learning processes involved in the phenomena observed in everyday interactions of toddlers with their verbal community and the learning processes involved in the experimental procedures.